Pengaruh Beban Kerja Terhadap Stres Kerja Karyawan Di PT Xyz Kabupaten Bandung - Nurhanifah, Hani; Irma Susanty, Ade (eProceedings of Management, 2023)
The purpose of this research is to find out and analyze how the level of employee workload, how employee work stress and the magnitude of the influence of workload on employee work stress at PT XYZ Bandung Regency. This research uses quantitative method with descriptive-causal type of research. Sampling was done by non-probability sampling method with the sampling technique used in this study is convenience sampling with the number of respondents as many as 96 people. The data analysis technique used is descriptive analysis and simple linear regression analysis. The results show that the workload has a significant effect on the work stress of PT XYZ Bandung Regency. This is evidenced by the results of the hypothesis test (t test) where t-count > t-table (11.370) > t-table (1.986) or p-value (0.000)Keywords-workload, work stress, human resources